Determining Program Priorities - Amy Harder (EDIS)
WC105, a 4-page fact sheet by Amy Harder, provides a step-by-step approach for sorting and prioritizing community needs for Extension programming. Includes references. Published by the UF Department of Agricultural Education and Communication, September 2010.